2011
DOI: 10.1186/1471-2164-12-144
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative miRNA Expression Analysis Using Fluidigm Microfluidics Dynamic Arrays

Abstract: BackgroundMicroRNAs (miRNAs) represent a growing class of small non-coding RNAs that are important regulators of gene expression in both plants and animals. Studies have shown that miRNAs play a critical role in human cancer and they can influence the level of cell proliferation and apoptosis by modulating gene expression. Currently, methods for the detection and measurement of miRNA expression include small and moderate-throughput technologies, such as standard quantitative PCR and microarray based analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 29 publications
0
93
0
1
Order By: Relevance
“…The system has successfully been used by other researchers. Jang et al (2011) measured the expression of microRNA and found that the sensitivity of the measurement increased compared with conventional singleplex RT-qPCR. They also measured higher fold changes than with an Affymetrix microarray.…”
Section: Introductionmentioning
confidence: 99%
“…The system has successfully been used by other researchers. Jang et al (2011) measured the expression of microRNA and found that the sensitivity of the measurement increased compared with conventional singleplex RT-qPCR. They also measured higher fold changes than with an Affymetrix microarray.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the desired cells are easily observed, allowing for their collection by LM and all materials in the plastic-embedded cell are captured since no etching is done (Figure 3). With the reduction of these technological limitations presented by small sample volume in transcriptional analyses, it is possible to study the interaction of plants in relation to model plant pathogens at high resolution without the loss of significant cellular information (Figure 4), making analyses of single cells possible (Abad et al 2008;Guo et al 2010;Citri et al 2011;Jang et al 2011;Byers et al 2012;Klink et al 2013;Livak et al 2013). Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The cost-and labor-intensiveness of RT-PCR may be partly overcome using multiplex technologies such as the Fluidigm microfluidic technology (Jang et al 2011). Using microarray technology allows for high-throughput global miRNA profiling but unlike RT-PCR is not quantitative and suffers from a lower sensitivity.…”
Section: Sample Collection Processing and Analysis Methodsmentioning
confidence: 99%